Development of Science Learning Parenting Model for Broken Home Learners through Website Learning Media - Rezeki, Sri Endah; Nugraha, Rahmad Agung; Apriani Fr, Dewi (Journal of English Language and Education, 2025)
The purpose of this study was to determine the needs of teachers and students for the development of a parenting model based on website media in improving science understanding and the involvement of broken home students in learning at SMPN 2 Tanjung Brebes, to describe the design of a parenting model that can support science learning for broken home students through the use of website learning media at SMPN 2 Tanjung Brebes and to determine the feasibility of a parenting model through the use of website learning media that can support science learning for broken home students at SMPN 2 Tanjung Brebes and to determine the effectiveness of a website-based science learning parenting model in improving the understanding and involvement of broken home students in science learning at SMPN 2 Tanjung Brebes. This study uses the Research and Development Method which aims to develop a science learning parenting model for broken home students through website media at SMPN 2 Tanjung Brebes. The results of the study indicate that in order to realize the objectives of this study from the results of in-depth research from various parenting model studies in the field of web-based science learning, namely analyzing the needs of teachers and students for the development of a website-based science learning parenting model at SMPN 2 Tanjung, creating a website design for a science learning parenting model to improve science learning achievement at SMPN 2 Tanjung, conducting a validity test on the science learning website, developing a science learning parenting model website using the ADD (Analysis, Design, Development) model at SMPN 2 Tanjung. Based on the results of the analysis, it shows that the needs of teachers and students for the development of media that can be used in learning in class and outside the classroom are very high.